Typology, management and smallholder farmer- preferred traits for selection of indigenous goats (Capra hisrcus) in three agro-ecological zones in the Democratic Republic of Congo - Simon, P.B.; Joseph, J.O.; Ochieng, J.W.; Tiambo, Christian K.; Tarekegn, G.M.; Machuka, Eunice M.; Kabange, D.; Musale, K.; Ciza, A.M.; Kizungu, R.V.; Pelle, Roger (Informa UK Limited, 2021)
The present study aimed to assess the typology, production management, and smallholder farmer-preferred traits in selecting indigenous goats in three agro-ecological zones (AEZs) in the Democratic Republic of Congo (DR Congo). Based on a structured survey, baseline data were recorded on 320 adults and unrelated does from 202 goat farms. Hierarchical clustering on principal components revealed three clusters in the goats studied well distinguished by double and triple kidding. Prolific goats mostly clustered into cluster two and three more represented by goats of South Kivu while 82.69% of goats in Tshopo were clustered into cluster one characterized by low reproductive performances. The Canonical Discriminant Analysis revealed that the body length was an important variable both to discriminate and to classify goats from the three AEZs. Goats from Kinshasa and South Kivu were not distanced while large distance was observed between goats from Kinshasa and Tshopo (F-stat, p < 0.001). While not subjected to any good management practices, goats were considered as a source of income and saving method in smallholder farmers’ households. Adaptability, resistance to disease and prolificacy were preferred traits by farmers in selecting goats. These results give the first step in the decision-making towards goat improvement in DR Congo.